Development and efficacy evaluation of remodeled canine parvovirus-like particles displaying major antigenic epitopes of a giant panda derived canine distemper virus - Zhao, Shan; Han, Xinfeng; Lang, Yifei; Xie, Yue; Yang, Zhijie; Zhao, Qin; Wen, Yiping; Xia, Jing; Wu, Rui; Huang, Xiaobo; Huang, Yong; Cao, Sanjie; et al. (Frontiers in Microbiology, 2023)
Canine parvovirus (CPV) and Canine distemper virus (CDV) can cause fatal diseases in giant panda (Ailuropoda melanoleuca). The main capsid protein of CPV VP2 can be self-assembled to form virus-like particles (VLPs) in vitro, which is of great significance for potential vaccine development. In the present study, we remodeled the VP2 protein of a giant panda-derived CPV, where the major CDV F and N epitopes were incorporated in the N-terminal and loop2 region in two combinations to form chimeric VLPs. The reactivity ability and morphology of the recombinant proteins were confirmed by Western blot, hemagglutination (HA) test and electron microscopy. Subsequently, the immunogenicity of the VLPs was examined in vivo. Antigen-specific antibodies and neutralizing activity were measured by ELISA, hemagglutination inhibition (HI) test and serum neutralization test (SNT), respectively. In addition, antigen specific T cell activation were determined in splenic lymphocytes. The results indicated that the VLPs displayed good reaction with CDV/CPV antibodies, and the heterologous epitopes do not hamper solubility or activity. The VLPs showed decent HA activity, and resembled round-shaped particles with a diameter of 22-26 nm, which is identical to natural virions. VLPs could induce high levels of specific antibodies to CPV and CDV, shown by the indication of neutralizing antibodies in both VP2N and VP2L VLPs group. In addition, splenic lymphocytes of mice immunized with VLPs could proliferate rapidly after stimulation by specific antigen. Taken together, the CPV VP2 VLPs or chimeric VLPs are highly immunogenic, and henceforth could function as CPV/CDV vaccine candidates for giant pandas.